Simulação de escavação escorada por meio de elementos isoparamétricos - Mitsuo, Tsutsumi (1975)
Elaboration of a computer program applying the Finite Element Method for the analysis of excavations in soils, struted or not. The general aspects of excavations simulation are discussed, taking into account the non-linear behavior of soil, the possibility of supporting structures and effects due temperature variations. An incremental analysis is made, which is able to simulate any construction sequence. The isoparametric quadratic element used confers considerable flexibility to the program. Some comparisons with actual cases are made.